1996
DOI: 10.1017/s0007485300039213
|View full text |Cite
|
Sign up to set email alerts
|

Influence of temperature and humidity on populations of Callosobruchus maculatus (Coleoptera: Bruchidae) and its parasitoid Dinarmus basalis (Pteromalidae) in two climatic zones of Burkina Faso

Abstract: Callosobruchus maculatus (Fabricius) develops in the seeds of Vigna unguiculata in the Sahel region of Africa. The reproductive activity of this species and the development of its offspring were studied during the dry season at Ouagadougou and Bobo Dioulasso (Burkina Faso), two zones with different climatic conditions. The length of imaginal life of the females and the developmental time varied with changes in climatic conditions, the lowest values for both parameters being found at the end of the dry season w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
69
0
3

Year Published

2001
2001
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(77 citation statements)
references
References 22 publications
2
69
0
3
Order By: Relevance
“…The time of introduction of the parasitoid wasps was very crucial in arresting the vulnerable stages of the bruchids which are the larval, the pre-pupa and the pupal stages. The introduction of parasitoids from three to six days (when the eggs are presumed hatched (Ouedraogo et al, 1996) to 20 days after the grains were infested apparently allowed for the proper life stage (early and late instar larvae) to be present for parasitization, and gave the parasitoid population a boost compared to the growth rate of the pest population. This study has also showed that the presence of more than one parasitoid in mixture gave more efficient control of the bruchids in the local bin than when one parasitoid species was present.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The time of introduction of the parasitoid wasps was very crucial in arresting the vulnerable stages of the bruchids which are the larval, the pre-pupa and the pupal stages. The introduction of parasitoids from three to six days (when the eggs are presumed hatched (Ouedraogo et al, 1996) to 20 days after the grains were infested apparently allowed for the proper life stage (early and late instar larvae) to be present for parasitization, and gave the parasitoid population a boost compared to the growth rate of the pest population. This study has also showed that the presence of more than one parasitoid in mixture gave more efficient control of the bruchids in the local bin than when one parasitoid species was present.…”
Section: Discussionmentioning
confidence: 99%
“…According to IITA (1989) C. maculatus consumes 50-90% of cowpea in storage annually throughout tropical Africa. The bruchid infestation also affects seed quality, market value and can reduce cowpea seed viability to 2% after three months of storage (Ofuya & Credland, 1995;Ukeh et al, 2011 Ouedraogo et al (1996) the life cycle of C. maculatus takes about 4-5 weeks and about 6-7 generations are quite common in many countries. A female lays about 90-100 eggs in her lifetime.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is a field -to-store pest as its infestation of cowpea often begins in the field as the mature pods dry (Huignard et al, 1985;Sathyaseelan et al, 2008) and when such seeds are harvested and stored, the pest population increases rapidly and results in total destruction within a short duration of 3-4 months (Rahman and Talukder, 2006). It multiplies very rapidly in storage and has caused 8.5% loss in pulses during postharvest handling and storage in India (Ouedraogo et al, 1996). Insect infestation is a major contributor of quality deterioration of durables (cereals, pulses, and tubers) stored in warm and humid climates.…”
Section: Introductionmentioning
confidence: 99%
“…of a particular place, which is governed by different geographical parameters (Murthy et al, 1996). Studies have shown the importance of seasonal variations in biology and development of insect (Odum, 1983;Ouedraogo et al, 1996). Insects are cold-blooded (Poikilothermic) organisms, so their body temperature is more or less same as that of their surrounding microenvironment.…”
mentioning
confidence: 99%